A narrativa de Euríbates na tragédia Agamemnon de Sêneca: um diálogo entre gêneros - Alves, Letícia Freitas (2015)
The play under analysis in this work, Agamemnon, written by Lucius Annaeus Seneca, depicts within its third act a long narrative (v.421-578), which is held by a messenger, Eurybates. Eurybates reports to the Queen of Argos, Clytemnestra, all the mishaps that the Greeks went through on their journey back from the Trojan War. The messenger’s speech is to some extent, due to its narrative-style story and its theme, a grand epic interlude within a tragedy. The existence of such a long epic interlude within a tragedy leads us to some questions: would Seneca be jeopardizing the laws of the tragic genre for building up a bigger epic narrative in this play? To what extent would Seneca take the well-known connection between the tragic and the epic in the Antiquity? Would Eurybates’ speech, once it has an epic nature, make allusion to epic poems and would they be important to the formation of meaning in Agamemnon ? How would a conjectural “epic speech” work in this tragedy? Thus this work proposes a study of Eurybates' speech from the point of view of the dialogue between the tragic and the epic genres and of the dialogue with other works, established, mainly, through allusions.